(untitled) (International Journal of Engineering and Computer Science, 2014)
Congestion is an aggregation of huge amount of data in the networks that results in delay in packet delivery ratio and even huge loss of data. Queue management is a technique to minimise the congestion rate so that the data is successfully transferred from the source and destination. There are two types of queue management techniques (a) In active queue management techniques the intimation is given by the queue to the senders to slow down the packet rate as its queue buffer is about to full (b) Passive Queuing the drops rate is more in comparison with active queuing because the senders does not have any idea about queue buffer size so they are not able to lower its delivery rate and queue buffer drops the received packet when the buffer is full.